Ulamas' and Professionals' Perceptions on the Islamic Inheritance Law under P.D. 1083 - Ayo, Abdulcader Maruhom (JPAIR Multidisciplinary Research, 2016)
The study was undertaken primarily to determine the perceptions of Ulamas and professionals on the level of awareness or knowledge and the level of acceptance of the Islamic Inheritance Law as codified in the Muslim Code of the Philippines. Using quantitative -qualitative methods, the 478 respondents Autonomous Region in Muslim Mindanao, starting in Lanao del Sur and Maguindanao, including Moro National Liberation Front (MILF)-controlled territory, up to Zamboanga del Sur, Sulu, and Tawi-Tawi participated the wide-range survey. Questionnaire, interview, focus group discussion, and observation were utilized in gathering the data. It was found that the respondents' level of awareness or knowledge on the Islamic Inheritance Law was only moderate. However, their knowledge of the Holy Qur'an and Sunnah as the primary sources of the law garnered a high level of awareness. As revealed in the interviews and focus group discussions, the overall moderate acceptance of the law is attributed to certain factors that could be broadly categorized into two sets: external and internal. A positive link between the respondents' level of awareness/knowledge and their level of acceptance of the Islamic Inheritance Law was found. This implies that an increase in the level of awareness may bring about an increase in the level of acceptance of the law.
Keywords: Social Science; Islamic Inheritance Law; mixed methods; Philippines